Implementation of Vaccination Policy for Controlling Foot and Mouth Disease in Livestock in the Fisheries and Service Office - Dede Jaenudin; Muhamad Husein Maruapey; R. Oetje Subagdja (Journal La Bisecoman, 2024)
This research is motivated by the problem of effectiveness, efficiency and distribution of vaccines for Foot and Mouth Disease (FMD) in livestock in Bogor Regency. The purpose of this study is to analyze how the implementation of vaccination policies on livestock in Bogor Regency and what factors support and do not support the implementation of FMD vaccination. This research uses a qualitative descriptive research method using the model developed by George C. Edward III that policy implementation is influenced by 4 factors. Edward III that policy implementation is influenced by 4 (four) variables, namely communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of FMD vaccination policy in Bogor District has been running well and successful in tackling FMD in livestock. The results include decreased FMD cases, improved livestock health and productivity. Communication, disposition, and bureaucratic structure variables are supporting factors for the successful implementation of FMD vaccination policy. Meanwhile, the resource dimension is a factor that does not support the implementation of FMD vaccination. This can be seen from the lack of staff (vaccination officers), inadequate vaccine storage (cool boxes), and lack of budget. Collaborative efforts with third parties (non-governmental organizations, private sector, universities) in terms of providing supporting facilities to ensure vaccine storage facilities meet the required standards and meet the availability of trained human resources.